Eight weeks of aerobic exercise, but not four, improves insulin sensitivity and cardiovascular performance in young women - Maha Sellami; Shamma Almuraikhy; Khaled Naja; Najeha Anwardeen; Hadaia Saleh Al-Amri; Mohammad Shoaib Prince; Amina Ali Aden; Alexander Doemling; Mohamed A. Elrayess (Scientific Reports)
Abstract Regular aerobic exercise has a significant impact on glucose metabolism and lipid profiles, contributing to overall health improvement. However, evidence for optimal exercise duration to achieve these effects is limited. This study aims to explore the effects of 4 and 8 weeks of moderate-intensity aerobic exercise on glucose metabolism, lipid profiles, and associated metabolic changes in young female students with insulin resistance and varying body mass, seeking to determine the optimal duration for physiological adaptations. Twenty-eight physically semi-active female students were randomly assigned to 4-week (G4, n = 13, age = 23.31 ± 5.19, BMI = 24.78 ± 5.87) and 8-week (G8, n = 15, age = 21.8 ± 2.56, BMI = 24.95 ± 4.81) training groups. The aerobic intervention maintained an intensity of 40–70% of maximum heart rate (HRmax). 6-min-walk test (6MWT), handgrip strength tests, insulin, HOMA-IR, lipid profiles, and metabolic profiles were assessed pre- and post-intervention. Following the intervention, G8, but not G4, exhibited a significant decrease in HOMA-IR (-14.59%, p = 0.047). The improvement in HOMA-IR was accompanied by notable improvements in 6-MWT (+ 38.18%, p < 0.001) and handgrip strength (+ 11.62, p = 0.027 and + 17.59%, p = 0.013), and increased levels of bilirubin degradation products, ribose, and glutarate. The elevated levels of bilirubin degradation products, known for their antioxidant properties, suggested a potential antioxidative response triggered by prolonged aerobic exercise. Additionally, an increase in ribose and glutarate indicated improved metabolic flexibility and enhanced utilization of alternative energy substrates. The 8-week aerobic exercise regimen demonstrated enhanced insulin sensitivity, upper body strength, and cardiovascular performance in young females compared to a 4-week regimen by triggering specific metabolic adaptations. These findings emphasize the complex relationship between exercise duration, metabolic adaptations, and overall well-being in young women, providing valuable insights for optimizing exercise prescriptions in promoting metabolic health.